The Influence of Interpersonal Relationships on Student Learning Outcomes - Okta Iswahyuningsih (Universitas PGRI SUMATERA BARAT, 2022)
This research is motivated by the presenceof students who have poor interpersonal relationship, such as poor communication between students and students, poor communication between students andteachers, studentswho have low report cards and students who are not open in terms of learning difficulties. This research uses descriptive quantitative method. The study population 282 students who were selected by using proportional random sampling teachnique. The research sample was 74 students. The instrument used was a questionnaire. Based on the research results obtained as follows : 1) interpersonal relationships with students are in the good category. 2) the learning outcomes of studentsare in the very high category. 3) there is an influence between interpersonal relationships on students learning outcomes with a result of 32% and the rest is influenced by other variables, in other words the accepted hypothesis says there is an influence of interersonal relationships on students learning outcomes in class VIII State Junior High School 12 Padang.